2022
DOI: 10.3389/fonc.2022.909035
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Sintilimab and Anlotinib as First Line Treatment for Advanced Hepatocellular Carcinoma (KEEP-G04): A Single-Arm Phase 2 Study

Abstract: PurposeImmune checkpoint inhibitors plus antiangiogenic tyrosine kinase inhibitors may offer a first-line treatment for advanced hepatocellular carcinoma (HCC). In this phase 2 trial [registered with clinicaltrials.gov (NCT04052152)], we investigated the safety and efficacy of first-line anti-PD-1 antibody sintilimab plus antiangiogenic TKI anlotinib for advanced HCC.Methods and MaterialsPathologically-proven advanced HCC patients received sintilimab (200 mg) on day 1 and anlotinib (12 mg) once daily on days 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 38 publications
4
20
2
Order By: Relevance
“…Trial of CheckMate040 has ushered the era of immunotherapy for HCC in the recent years, but phase III CheckMate459 trials of PD-1 inhibitors monotherapy for HCC have all failed to meet the primary endpoints (5). Dual combination regimen, such as lenvatinib plus pembrolizumab, camrelizumab plus apatinib, and sintilimab plus anlotinib, have yielded promising clinical efficiency and safety, but the prognosis for those u-HCC patients is still unsatisfactory with the median OS of 20.1 to 20.4 months (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Trial of CheckMate040 has ushered the era of immunotherapy for HCC in the recent years, but phase III CheckMate459 trials of PD-1 inhibitors monotherapy for HCC have all failed to meet the primary endpoints (5). Dual combination regimen, such as lenvatinib plus pembrolizumab, camrelizumab plus apatinib, and sintilimab plus anlotinib, have yielded promising clinical efficiency and safety, but the prognosis for those u-HCC patients is still unsatisfactory with the median OS of 20.1 to 20.4 months (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…This trial demonstrated the tolerability and efficacy of anlotinib in combination with ICI therapy for cervical cancer [240]. Sintilimab plus anlotinib also demonstrated good treatment efficacy and tolerability in both advanced hepatocellular carcinoma (NCT04052152) and advanced non-small cell lung cancer (NCT03628521) [241,242].…”
Section: Combination Of Normalization Strategiesmentioning
confidence: 84%
“…Sintilimab is a PD-1 antibody approved in China for the treatment of NSCLC, Hodgin's lymphoma, hepatocellular carcinoma, and esophageal squamous cell carcinoma (ESCC) (25). Recently, the combination of sintilimab and anlotinib has shown promising antitumor activity and tolerable safety profiles in cervical cancer, endometrial cancer, hepatocellular carcinoma, and biliary tract cancer (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%